New pathways and mechanisms regulating and responding to Delta-like ligand 4-Notch signalling in tumour angiogenesis. - Oon, C; Harris, A (2011)
Notch signalling is a key pathway controlling angiogenesis in normal tissues and tumours. This has become a major focus of development of anticancer therapy, but to develop this appropriately, we need further understanding of the mechanisms of regulation of Dll4 (Delta-like ligand 4), a key endothelial Notch ligand. Dll4 and VEGF (vascular endothelial growth factor) cross-talk, with VEGF up-regulation of Dll4 and Dll4 down-regulating VEGFR (VEGF receptor) signalling. Both are essential for normal angiogenesis, and blockade of one may produce compensatory changes in the other. The present review considers recent developments in the regulation of Dll4 expression and functions, its role as a mechanism of resistance to anti-angiogenic therapy, and methods needed to develop effective therapy against this target.